Internet of Things : a gateway centric solution for providing IoT connectivity - Karhula, Pekka (2016)
The Internet of Things (IoT) is revolutionising the traditional Internet by extending it with smart everyday objects. Wearables, smart grids and home automation systems are just a few examples of the IoT. A noteworthy point is that the amount of devices connected to the Internet will rapidly grow with the IoT. The IoT typically involves devices that are constrained in terms of energy, memory and processing resources. Therefore, they also limit applying the existing Internet protocols to the IoT. New protocols have been designed for the IoT, all the way from the physical layer, to the application layer. This thesis presents an implementation for an IoT gateway, which enables connectivity to the Internet for several different end devices using protocols designed for the IoT. This thesis reviews existing IoT architectures, protocol stacks, IoT gateway functionalities and management, and presents three case examples of gateway usage scenarios.